1984
DOI: 10.1136/adc.59.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Blood spots on Guthrie cards can be used for inherited tetrahydrobiopterin deficiency screening in hyperphenylalaninaemic infants.

Abstract: SUMMARY We describe a method of screening for dihydropteridine reductase deficiency and dihydrobiopterin synthesis deficiency-the two inherited defects that cause tetrahydrobiopterin deficiency-using blood spots on Guthrie cards. Dihydropteridine reductase deficiency may be identified positively, and a biopterin value of <6-0 [ig/l in the presence of hyperphenylalaninaemia indicates further investigation for dihydrobiopterin synthesis deficiency.Tetrahydropbiopterin deficiency can arise from defective synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In the UK, investigation of patients with HPA for BH 4 deficiency is by a combination of total biopterin and DHPR assay in eluates from dried blood spots on filter paper cards. The manual DHPR assay (Leeming et al, 1984) used initially for this screening service is labour-intensive and unsuited to our workload. Spuriously low activity can be obtained if there is insufficient blood on the card or poor recovery of blood on elution, a problem exacerbated by international variation in absorption and thickness of filter paper card used.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, investigation of patients with HPA for BH 4 deficiency is by a combination of total biopterin and DHPR assay in eluates from dried blood spots on filter paper cards. The manual DHPR assay (Leeming et al, 1984) used initially for this screening service is labour-intensive and unsuited to our workload. Spuriously low activity can be obtained if there is insufficient blood on the card or poor recovery of blood on elution, a problem exacerbated by international variation in absorption and thickness of filter paper card used.…”
Section: Discussionmentioning
confidence: 99%
“…11,46,[81][82][83] Random urine specimens dried on filter paper can also be used, with the advantage that they can be mailed unfrozen. [84][85][86] Samples are oxidized to convert BH 4 , q-BH 2 , and BH 2 to total biopterin, and dihydroneopterin to neopterin. Separation by HPLC then results in pterin profiles characteristic for each form of HPA (Fig.…”
Section: Urinary Pteridine Profilementioning
confidence: 99%
“…Neonatal screening programme revealed that hyperphenylalaninaemia (Hphe) can be caused by absence of any one of the three known essential components of the Phe hydroxylating system (Jervis, 1947;Kaufman, 1978;Scriver & Clow, 1980a, b;Dhond, 1984;Dhond«a/., 1985;Kaufman, 1985;Takahashi ^ra/., 1985;Danks ef a/., 1978;Danks & Cotton, 1980;Curtius et al, 1985;Danks, 1978;Kaufman et al, 1975;Lon$hi etal., 1985;Pfleiderer, 1978;Niederwiesereza/., 1984): (1) inactivation of the Phe hydroxylase (classical PKU); (2) impaired biosynthesis of tetrahydrobioptcrin (BH4); or (3) inactivation of dehydropteridine reductase (DHPR). Identification and treatment of BH4 deficiencies are essential, and have recently become an additional function of screening centers (Firgaira et al, 1979;Niederwieser et al, 1982;Narisawa et al, 1983;Leeming et al, 1984;Matalon, 1984;Sahota et al, 1985).…”
Section: Introductionmentioning
confidence: 99%